Endovascular Recanalization of a Thrombosed Portocaval Hemitransposition Graft in a Liver Transplant Recipient - Kumar, Saurabh; Batra, Apoorva; Makki, Kausar; Vij, Vivek (Journal of Clinical Interventional Radiology ISVIR, 2025)
Portal vein thrombosis was historically considered a contraindication for liver transplantation. However, recent technical advancements have enabled surgeons to manage this complication through various innovative approaches. One such technique is portocaval hemitransposition, particularly applicable in cases of extensive porto-splanchnic thrombosis. This procedure involves utilizing the recipient's inferior vena cava to perfuse the portal vein of the liver graft. We report a case of acute thrombosis of a portocaval hemitransposition graft that was successfully managed with catheter-directed thrombolysis, angioplasty, and stent placement.
Keywords: portocaval hemitransposition; portal vein thrombosis; liver transplantation